Stop acting rich : --and start living like a real millionaire - Stanley, Thomas J. (John Wiley & Sons, 2009)
"A leading expert on the affluent reveals the real way to build wealth With well over two million of his books sold, and huge praise from many media outlets, Dr. Thomas J. Stanley is a recognized and highly respected authority on the wealthy, their behavior, and their thinking. Now, in Stop Acting Rich, he details how the less affluent have fallen into the elite luxury brand trap that keeps them from truly acquiring wealth and details how to get out of it by emulating the working rich as opposed to the super elite. A defensive strategy for tough times, Stop Acting Rich will show you how to live like Warren Buffett-a rich, happy life-through accumulating more wealth and using it to achieve the type of financial freedom that will create true happiness and fulfillment. Puts wealth in perspective and shows you how to live rich without spending more Details why we spend lavishly and how to stop this destructive cycle Discusses how being "rich" means more than just big houses and luxury cars Other titles by Stanley: The Millionaire Mind and The Millionaire Next Door It's time to understand why we buy what we buy, so that we can start accumulating, rather than depleting, wealth. Stop Acting Rich shows you exactly what it takes to achieve this elusive goal"--Provided by publisher